Government Bank & Regional Development Bank: A Sustainable Development Financing Synergy - Nandiwardhana, Aditya Pratama; Putra, Yananto Mihadi; Yuniarto, Hendy; Malima, Gabriel Clement (Baca Dulu Publisher, 2025)
Global warming and climate change caused by emissions are currently a priority concern for the world because they will have a direct and significant impact on the survival of all living things. As financial institutions that provide financing to the industrial sector, government banks and regional government banks financing can potentially develop the Indonesian economy while having a negative impact on emissions from industrial sector activities. By adopting the Vector Error Correction Model (VECM), this reserach reveals that government banks and regional government banks have a significant impact to the sustainable development index. However, in addition to the two types of banks only identified as short-term financing, the proportion of influence generated sequentially for government banks and local government banks are only 13% and 11%. Finally, the need for large funds and a long financing repayment period are significant aspects in building a more sustainable industrial and economic climate.